1994
DOI: 10.3354/meps109115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an artisanal fishery on the fish and urchin populations of a Kenyan coral reef

Abstract: An investigation of the effects of artisanal fishing on coral reef fish assemblage structure was undertaken through a comparison of fish stocks on 2 apparently identical sets of reefs, one (within the Kisite Marine National Park) on w h c h all fishing is prohibited, and one (within the Mpunguti Marine National Reserve) on which artisanal fishing only is allowed. Replicate visual censuses of fish along 250 X 10 m band transects at 6 intensive study sites demonstrated that there were large differences in popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 12 publications
3
29
1
Order By: Relevance
“…Fishing can also have indirect effects on predatory fish communities. For example, removal of large-bodied predators may have allowed smaller ones to increase in abundance due to release from competition or predation [30,61,62]. Indeed, the relatively unfished trumpetfish, and the two smallest species of both grouper (i.e., graysby and coney) and snapper (i.e., lane and mahogany snappers) were found to increase in presence with decreasing presence of large predators (Table 3, Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Fishing can also have indirect effects on predatory fish communities. For example, removal of large-bodied predators may have allowed smaller ones to increase in abundance due to release from competition or predation [30,61,62]. Indeed, the relatively unfished trumpetfish, and the two smallest species of both grouper (i.e., graysby and coney) and snapper (i.e., lane and mahogany snappers) were found to increase in presence with decreasing presence of large predators (Table 3, Figs.…”
Section: Discussionmentioning
confidence: 99%
“…As maximum size is correlated with many other life-history traits, resulting in larger fish being more vulnerable to exploitation (Jennings et al 1999, Denny et al 2002 and because larger fish are generally targeted before smaller fish (Pauly et al 1998), size is proving to be a useful way to assess multispecies fisheries (Bianchi et al 2000, Dulvy et al 2004, Graham et al 2005. Increasing evidence of species-level (Watson and Ormond 1994, Graham et al 2003) and aggregated size-based (Dulvy et al 2004) indirect interactions within coral reef fish assemblages further suggest that recovery trajectories in these ecosystems should be assessed at the assemblage level.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…As maximum size is correlated with many other life-history traits, resulting in larger fish being more vulnerable to exploitation (Jennings et al 1999, Denny et al 2002 and because larger fish are generally targeted before smaller fish (Pauly et al 1998), size is proving to be a useful way to assess multispecies fisheries (Bianchi et al 2000, Dulvy et al 2004, Graham et al 2005. Increasing evidence of species-level (Watson and Ormond 1994, Graham et al 2003) and aggregated size-based (Dulvy et al 2004) indirect interactions within coral reef fish assemblages further suggest that recovery trajectories in these ecosystems should be assessed at the assemblage level.This study examines the size structure and biomass of coral reef fishes in Kenyan coral reefs by examining 4 fully closed MPAs that vary in their time of establishment (from 1968 to 1991) with data that are available from 4 yr prior to and 36 yr after closed-area management (see Table 1). The study sites were examined between 1987 and 2004, and repeatedly sampled so that a 40 yr chronosequence of management can be patched together from this sampling and differences in the starting dates for closed-area management.…”
mentioning
confidence: 99%
“…[45,56,66,105]) or coral reefs (e.g. [65,91,[106][107][108][109][110]), there was a general lack of data quantifying the relationship between biota and habitat structure inside and outside the MPA (but see [45,91,101,[108][109][110][111][112]). We could only identify 'habitat-confounded' studies with confidence when the authors explicitly reported significant differences in habitat among the sites studied inside and outside the MPA.…”
Section: Key Challenges Met In This Reviewmentioning
confidence: 99%